Introducing a Symmetry-Breaking Coupler into a Dielectric Metasurface Enables Robust High-Q Quasi-BICs - Moretti, Gianni Quimey (2022)
Dielectric metasurfaces supporting quasibound states in the continuum (quasi-BICs) exhibit very high-quality factor resonances and electric field confinement. However, accessing the high-Q end of the quasi-BIC regime usually requires marginally distorting the metasurface design from a BIC condition, pushing the needed nanoscale fabrication precision to the limit. This work introduces a novel concept for generating high-Q quasi-BICs, which strongly relaxes this requirement by incorporating a relatively large perturbative element close to high-symmetry points of an undistorted BIC metasurface, acting as a coupler to the radiation continuum. This approach is validated by adding a ≈100 nm diameter cylinder between two reflection-symmetry points separated by a 300 nm gap in an elliptical disk metasurface unit cell, using gallium phosphide as the dielectric. It is found that high-Q resonances emerge when the cylindrical coupler is placed at any position between such symmetry points. This metasurface´s second harmonic generation capability in the optical range is further explored. Displacing the coupler as much as a full diameter from a BIC condition produces record-breaking normalized conversion efficiencies >102 W−1. The strategy of enclosing a disruptive element between multiple high-symmetry points in a BIC metasurface can be applied to construct robust high-Q quasi-BICs in many geometrical designs.